Studi pertumbuhan dan evaluasi parameter tumpangsari kubis bunga (Brassica oleracea L.) dengan tanaman legum - Devie Rienzani Supriadi; Ekalia Yusiana (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
This research aims to determine the growth and evaluate the parameters of Cauliflower (Brassica oleracea L.) planted with several legume plants at different levels of plant density. The research was conducted in Telukjambe Village, East Telukjambe District, Karawang Regency in December 2022 – March 2023. The research used an experimental method with a single-factor Randomized Group Design (RAK) with 3 sets of experimental designs, each consisting of 5 proportion treatments. inter-cropping and repeat 5 times. The treatment given is; K1= 100% cauliflower , K2= 25% cauliflower + 75% legumes, K3= 50% cauliflower + 50% legumes, K4 = 75% cauliflower  + 25% legumes, K5= 100% legumes. The first set of experimental designs is a system of inter-cropping cauliflower with soybeans, the second experimental set is a system of inter-cropping cauliflower with peanuts and the third experimental set is a system of inter-cropping cauliflower with green beans. The research results were analyzed using the F test at a level of 5% and a Least Significant Difference (BNT) further test at a level of 5%. The results showed that inter-cropping of cauliflower and soybeans (experimental set 1) provided beneficial results compared to inter-cropping with peanuts and green beans. The results can be seen from the LER and RCC values for all proportions of planting number or plant population density levels > 1. The highest LER and RCC values for inter-cropping cauliflower and soybeans (experimental set 1) were shown in the K3 treatment (50% Cauliflower + 50% Soybeans) namely 1.49 and 10.8.